What Price Security? - Donald C. Masters (Journal of Strategic Security, 2009)
This article presents a critique of the Copenhagen Consensus Center's(CCC) exhaustive study on transnational terrorism, published in 2008.The implications of this study are controversial, yet highly relevant in today's economic environment. The Obama administration must come toterms with fiscal realities that will challenge budget priorities and invigorate what will undoubtedly prove to be tough negotiations on Capitol Hill for homeland security dollars. It is proposed here that standard economic tools such as benefit cost analysis, cost effectiveness criteria, and simulation models can help identify areas where security can be either extended or improved using fewer resources. Greater movement towards competitive procurement practices will also result in lower costs and higher returns on security investments.